(untitled) (ModaPalavra e-periódico, 2012)
Are described by this study initiatives of a clothing company midrange, the State of Santa Catarina, aiming to organizational learning. Through the case study, it was found that this company invests in the learning of their employees, with initiatives that provide sharing of internal information and external acquisition of new knowledge in event source technical, artistic, individual skills, cultural, fairs and discussions of teamwork.